Maize nutrient dynamics: growth, yield and sustainable practices: A narrative review - Osman, Magdoline Mustafa Ahmed; Kuunya, Ronald; Alrasheed, Raina; Hassan, Mohammed M.; Wasikoyo, Erastus; Gumisiriya, Costa; Mudawi, Hanan ibrahim; Elsalahi, Randa; Rátonyi, Tamás (Acta Agraria Debreceniensis, 2025)
Nutrient acquisition is the fundamental regulator of maize (Zea mays) growth, development, and yield. The present narrative review intends to integrate existing information on dynamics of nutrient uptake in maize under scrutiny for understanding how the processes affect growth and yield. We focus on the effective absorption and utilization of macronutrients (N, P and K) and micronutrients that promote plant health, grain development, and stress tolerance. Key determinants of nutrient availability (soil type, pH, organic matter, environment) and physiological or yield impacts of deficiency are studied. Strategies to optimize uptake efficiency precision application of fertilizer, organic fertilizers, and sustainable soil management are discussed. Optimizing these dynamics is central to maize productivity, enhancement and sustainable crop production. This review provides valuable insights into optimizing maize nutrition for improved food security and sustainable crop production.